The Nature and Ethical Dimensions of Work in Surah al-Tawbah, Verse 105 - Ulfa Kurnia; Akbar Bin Asis (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
The discussion in this treatise is the Qur'an's view of work ethics focusing on Surah Al-Taubah /105:9, with this writing in the study of interpretation can provide understanding for the community to do a good job. This study uses a qualitative literary research method. Then the data collection used is the library method that comes from primary and secondary data. After the data is collected, it is then performed by processing the data using a perfect interpretation pattern. Furthermore, the data were analyzed using description, validation and argumentation. The results of this study, in work ethics in Surah At-Tawbah /105:9 found forms of work ethics, working hard, enthusiasm and wisdom for life as a quality virtue of life in the sense that it should be with good efforts and methods and to be grateful for what is achieved as a form of human existence.